Attitudes and knowledge in high school science: an empirical test of a theoretical model of correlations - Quirós Ruiz, Óscar Enrique (2023)
It has been discussed that emotional investment in the educational process generates positive cognitive outcomes. This correlation addresses a core tenet of the three learning domains, Cognitive, Affective, and PsychoMotor where all three constitute separate areas of one single learning process. And as such, one would expect to be able to measure this correspondence between the three domains. This study attempts to test the hypothesis of a correlation between the cognitive and affective domains in a cohort of in-service science teachers. Specifically, we seek to assess whether the affective posture towards school sciences shows an association with their cognitive competence in biology, chemistry and physics. We used partial least square regression analysis to examine the data, and the results indicate a direct correlation between the affective and cognitive domains. Teachers who scored higher in cognitive tests for the three sciences also had a more positive attitude towards them. These findings provide strong empirical evidence in support of the theoretical principle that the three domains are separate but interconnected components of the educational process.